Six Cognitive Stages (Reconstruction of Jean Piaget's Cognitivism Educational Theory) - Muhammad Fuad Ikhwansyah; Nashifuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Palangkaraya, 2026)
Education has a significant influence on human beings. Therefore, numerous developments can be found within the realm of education itself, one of which concerns educational theory. Many educational theories have been proposed, among which the most intriguing is the Cognitive Developmental Theory by Jean Piaget. This theory details the stages of an individual's cognitive development into four stages from birth to adulthood. However, in the realm of adulthood, it appears that Jean Piaget has not yet detailed two main stages. Consequently, researchers reconstructed the theory into six stages. This research employs a qualitative approach with data collection methods utilizing literature review. The analysis method used is literature analysis. The research results conclude that the six stages of the reconstructed Jean Piaget theory include: sensorimotor or the stage of motor and physical schema (from birth to 2 years), preoperational or the initial stage of thinking and understanding symbols (2 to 7 years), concrete operational or the stage of starting to think systematically, especially regarding concrete and objective matters (7 to 11 years), formal operational or the development of the ability to think systematically and abstractly (11 to 40 years), intermediate operational or the peak of cognitive ability (40 to 60 years), and post-operational or the decline in cognitive ability (> 60 years).